FILANTROPI ISLAM DAN PEMBERDAYAAN EKONOMI - Saripudin, Udin (BISNIS, 2016)
Poverty is an interesting theme discussed especially among social scientists. Before getting to know scientific studies on the issue of poverty, the community has been running a tradition to respond to the problems of poverty in the form of giving. The "give" in its various forms is not limited in the form of money orgoods but also the work or efforts to ease the burden on the poor and improve their well-being referred to as philanthropy. With descriptive methods this paper seeks explain and explore how the link between philanthropy Islam (zakat, donation and charity) and poverty reduction that occurs in a country, so therole of zakat, donation and charity as an instrument of distributive justice can be felt by the poor.